Scalling Gaius and Diotrephes : Socio-economic Stratification in 1 and 3 John - Carman, Jon-Michael
The Johannine epistles offer a glimpse into the real-life struggles of early Jesus followers. And yet, for all the insight these letters provide into the going-on of such communities, what they may say regarding the issue of socio-economic scaling and/or stratification is seldom pursued. Though scholars do occasionally make mention of the presence of wealthy members in the community on the basis of language in 1 Jn 3:17 and the presence of Gaius and Diotrephes in 3 John, little is said beyond the fact that there might be some 'wealthy' church members. Thus, in the present study I propose to take what little can be said about the Johannine epistles regarding their socio-economic setting and bring it into conversation with Longenecker's work on wealth scaling in order to help put as fine a point as possible on what one might ascertain about social stratification in 1-3 John. Furthermore, the claim that Gaius is a wealthy householder, a position generally assumed rather than argued, is bolstered through an analysis of demographic data and the financial costs associated with hospitality.
Keywords: 1 John; 3 John; Johannine Epistles; Socio-economic